Aplicación de un manual de desarrollo de habilidades cognitivas que propicien la metacognición en los niños y niñas de 4-5 años en la sala de estimulación temprana, en la carrera de parvularia, parroquia Eloy Alfaro, cantón Latacunga provincia de Cotopaxi durante el periodo 2011-2012 - Alvarez Rea, Jéssica Jeaneth (2015)
This research conducted at the Technical University of Cotopaxi during the period 2011-2012, aims to develop cognitive skills through playful activities that encourage better learning cycle in children/as 4-5 years. The problem was observed in both students and teachers had no place of learning, such activities will help promote the theoretical and practical knowledge. To do this takes into account the participation of the university community, after approving the macro project proposed by the directors of the race of Preschool it accessed compliance with the implementation of the Board of early stimulation for educational benefit. Using research techniques: the survey, interviews, analysis and interpretation of data and concluded: When handling manual cognitive skills development ranging from pre teachers obtain a clear knowledge necessary to assist in the education of young children to perform activities and improve the methodological strategies.